2015
DOI: 10.1002/bjs.9806
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and consequences of conversion in laparoscopic major liver resection

Abstract: Conversion during LMH should be anticipated in patients with raised BMI, large lesions and biliary reconstruction. Conversion does not lead to increased morbidity compared with planned laparotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 34 publications
5
49
1
2
Order By: Relevance
“…The IC and DSS incorporate liver function, tumor features, and surgical characteristics. However, other factors, such as neo‐adjuvant chemotherapy, previous liver resection(s), obesity, and age, are known to significantly impact LLR . Recently, a survey was published involving 80 surgeons with a combined experience of more than 7,000 LLR procedures .…”
Section: Discussionmentioning
confidence: 99%
“…The IC and DSS incorporate liver function, tumor features, and surgical characteristics. However, other factors, such as neo‐adjuvant chemotherapy, previous liver resection(s), obesity, and age, are known to significantly impact LLR . Recently, a survey was published involving 80 surgeons with a combined experience of more than 7,000 LLR procedures .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bleeding was considered among the most common reasons for conversion. 38,39 Dagher et al 15 reported 20 cases of LRH, 2 (10%) of which required conversion to laparotomy, including one case of continuous diffuse bleeding during parenchymal transection. Lainas et al 20 performed LRH to treat colorectal liver metastases and reported that 5 (11.1%) out of 45 patients required conversion to open surgery owing to intraoperative bleeding (>900 mL), also during parenchymal transection.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing non-surgical policies for benign lesions should be expected and adaptive strategies based on the natural history of malignant diseases will avoid futile surgeries such as some multiple CRLM controlled by chemotherapy (5). In the end, surgeons should never forget that a justified non-operative approach will always be less invasive than the least invasive surgical approach.…”
Section: Editorial On Techniques and Innovations In Liver Surgerymentioning
confidence: 99%